Experimental study of hydrogen generation from in-situ heavy oil gasification. (1st April 2022) - Yang, Simin; Huang, Siyuan; Jiang, Qi; Yu, Chunsheng; Zhou, Xiang
Highlights: More than 80% of the total hydrogen generation comes from the coke dehydrogenation reaction. Coke is mainly generated in the pyrolysis stage and the quantity and quality of coke is mainly determined by asphaltenes. A heavy oil gasification kinetic model is proposed based on the TGA-MS experiments. Abstract: Heavy oil in-situ gasification technology (ISG) produces hydrogen by injecting air and water into the formation and chemically react with the heavy oil, which can efficiently exploit oil and gas resources in the form of clean energy. The pyrolysis reaction of crude oil is particularly important for this technology regarding hydrogen generation. In this research, the mechanisms of hydrogen generation from heavy oil pyrolysis were investigated based on the thermogravimetric analyzer (TGA) and mass spectrometer (MS). The experimental results show that the weight loss of heavy oil under 25–900 °C can be divided into two stages. The first stage is mainly the evaporation of light fractions, which corresponds to the physical stage. The second stage contains pyrolysis and coke dehydrogenation reactions, which is considered as the chemical stage. Also, the study indicates that the hydrogen generation occurs in both pyrolysis and coke dehydrogenation reactions, and 80% of hydrogen is generated from the coke dehydrogenation reaction with corresponding reaction temperature range of 528–820 °C. Furthermore, the kinetic parameters of heavy oil pyrolysis were obtained based on the distributed activation energy model (DAEM), where the apparent activation energy of the coke dehydrogenation reaction is greater than 350 kJ/mol, and the reaction frequency factor (k0 ) is greater than 2.83 × 10 23  s −1 . The reaction kinetic parameters obtained in this paper and the established law of hydrogen generation by heavy oil under thermal effect lay the foundation for further research on ISG technology.